Predictors of and survival after incident stroke in type 1 diabetes. (January 2013) - Secrest, Aaron M; Prince, Catherine T; Costacou, Tina; Miller, Rachel G; Orchard, Trevor J
Few studies have examined stroke risk in type 1 diabetes mellitus (T1DM). Stroke incidence, predictors, and survival were thus explored in this study. Pittsburgh Epidemiology of Diabetes Complications (EDC) Study participants ( n = 658) with childhood-onset T1DM were followed biennially for 18 years. Baseline (1986–1988) mean age and diabetes duration were 28 and 19 years respectively. Stroke incidence and type was determined via survey or physician interview and, when possible, confirmed with medical or autopsy records. During follow-up, 31 (4.7%) strokes occurred (21 ischaemic, 8 haemorrhagic, 2 unclassified) in participants of mean age = 40.2 years (range 23–60). In exploratory multivariable Cox modelling, diabetes duration, systolic blood pressure (SBP), non-high density lipoprotein cholesterol (non-HDLc), white blood cells (WBC), and pulse significantly predicted ischaemic stroke. Adding overt nephropathy (ON) (hazard ratio = 4.4, 95% CI, 1.5–12.4) to the model replaced SBP. Participant survival after stroke was 80.6%, 45.2%, and 9.6% at 1, 5, and 10 years, respectively, and significantly worse after haemorrhagic stroke ( p = 0.03). These risk factors merit careful evaluation and management to prevent stroke in T1DM, which occurs at least 20 years earlier than in the general population.